GEOLOGICAL AND ECONOMIC ASSESSMENT OF GROUNDWATER: NATIONAL AND INTERNATIONAL TAXONOMIES IN ESTIMATING RESERVES AND RESOURCES - Luibchyk, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The objective of the study is to examine major differences and similarities in domestic and international methodological approaches to estimating groundwater resources and reserves. Contrastive analysis of the most popular international classification system of mineral reserves and resources was carried out, the system of McKelvey and CRIRSCO are described. The comparison between the Ukranian Classifications systems of reserves and resources of drinking and industrial water and the United Nations Framework Classification for Fossil Energy and Mineral Reserves and Resources – 2009 (UNFC-2009) has been done. The harmonization between UNFC-2009 and the Ukrainian Classification is based on the unified approaches to the qualification of the reserves/resources on the basis of three common key characteristics that reflect: degree of geological knowledge (G axis), degree of technical and economic assessment (field project status and feasibility) (F axis), level of commercial value (economic and social viability) (E axis). The main difference between these two classification consist in conditions origin. The Ukrainian Classification was developed in the Soviet command planning system and the UNFC-2009 from the beginning focused on the market system. Therefore, the criteria for classification criteria "commercial value" in the national classification was developed worse. Instead, the criteria for "degree of scrutiny geological" was fully developed in comparison to international classifications. The practical significance of this analysis is to implement the global trend of globalization of international classification systems and establish an international classification of reserves and mineral resources for the formation of a standard reporting system. In 2009, classification framework of the United Nations was developed, whose mission – to build tools for the classification of reserves/resources of minerals based on internationally uniform system based on market economy criteria. Most countries have not only recognized the UNFC, but also significantly changed their national classification. Despite the fact that the theme of "comparison criteria for domestic and international classifications of reserves and mineral resources" was devoted a lot to research – underground water remained unaddressed.